Komodifikasi Tubuh dalam Narasi "Pemersatu Bangsa" pada Kampanye Lingkungan: Analisis Wacana Kritis Konten Pandawara - Adinda Erliana Romadhon; Rizky Maulana (Kajian Administrasi Publik dan ilmu Komunikasi, 2025)
This study examines the commodification of women’s bodies within environmental campaign content on digital media, focusing on a video produced by Pandawara Group that addresses textile waste issues. Although the campaign aims to raise ecological awareness, the visual emphasis on a female body particularly the exposure of a bra redirected public attention from environmental messages to sexualized interpretations in the comment section. This research aims to analyze how such meaning shifts occur through representation and audience interpretation. Using Sara Mills’ Critical Discourse Analysis, this study focuses on subject–object positioning and reader positioning in both visual and verbal elements of the content. The data consist of one campaign video and selected public comments on TikTok, analyzed qualitatively. The findings reveal that women are positioned as visual objects rather than active subjects within the discourse, while audiences are constructed as observers of the female body instead of interpreters of environmental issues. The recurring use of the phrase “content that unites the nation” further legitimizes sexualized readings and reinforces dominant gendered discourse. Importantly, the study finds that such interpretations are reproduced not only by male audiences but also by female users, indicating the internalization of dominant visual culture in digital spaces. This study contributes to gender and media studies by demonstrating that environmental campaigns are not free from gender bias and that visual representation plays a crucial role in shaping unintended meanings within social campaigns.